The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1987
DOI: 10.1104/pp.84.2.240
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Pod Set Enhancement with Synthetic Cytokinin Analogs

Abstract: The previously reported activity of benzyladenine and selected other cytokinin analogs to increase pod set in soybean (Glycine max [L.I Merr.) was further investigated to define the structure-activity relationship and evaluate the effects of the cytokinins on yield parameters. Enhancement of pod set was found to be greatest with N-6 saturated alkyl substituted analogs, and was only weakly associated with activity in a callus growth bioassay. The response of yield parameters to increasing pod load was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
0
5

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 8 publications
4
20
0
5
Order By: Relevance
“…Several previous studies indicated that cytokinin plays a critical role in pod set (Crosby et al, 1981;Dyer et al, 1987;Peterson et al, 1990;Mosjidis et al, 1993;Kokubun and Honda, 2000;Nagel et al, 2001). Therefore, we examined whether pod number can be increased by applying cytokinin to the plants with a high source/sink ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies indicated that cytokinin plays a critical role in pod set (Crosby et al, 1981;Dyer et al, 1987;Peterson et al, 1990;Mosjidis et al, 1993;Kokubun and Honda, 2000;Nagel et al, 2001). Therefore, we examined whether pod number can be increased by applying cytokinin to the plants with a high source/sink ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous cytokinins detected in exudate showed a maximum concentration during a period from 0 to 9 days after anthesis, when most fl owers are destined to either initiate or abort pods (Heindl et al, 1982;. The application of BA to racemes reduced abortion and increased pod number (Crosby et al, 1981;Carlson et al, 1987;Dyer et al, 1987;Peterson et al, 1990;Mosjidis et al, 1993;Reese et al, 1995;Nagel et al, 2001). Within individual racemes, pod set probability at different fl oral positions was closely associated with the cytokinin concentration (Kokubun and Honda, 2000).…”
mentioning
confidence: 99%
“…Alguns estudos têm mostrado uma forte tendência tecnológica para o uso de citocininas sintéticas, aplicadas via foliar, associadas ou não a nutrientes, como formas de manejo para aumentar a produtividade da soja (Crosby et al, 1981;Carlson et al, 1987;Dyer et al, 1987;Mosjidis et al, 1993;Nagel et al, 2001;Cho et al, 2002;Liu et al, 2004;Yashima et al, 2005;Nonokawa et al, 2007). Nessa leguminosa, um elevado número de flores e de legumes jovens é abortado naturalmente, o que representa um impacto negativo na produtividade (Nonokawa et al, 2007).…”
Section: Kinetin and Potassium Nitrate Effects On Agronomic Characterunclassified
“…Os principais fatores envolvidos na fixação de legumes de soja são a disponibilidade de nutrientes e de fotoassimilados destinados a esses legumes, quando em desenvolvimento (Wiebold, 1990), assim como a disponibilidade de algumas classes de hormônios nas sementes (Crosby et al, 1981;Carlson et al, 1987;Kokubun & Honda, 2000;Yashima et al, 2005). Pesquisas indicam a existência de deficiência de citocinina endógena, no terço superior do racemo em plantas de soja, que se encontra correlacionada ao maior aborto das partes reprodutivas da planta (Kokubun & Honda, 2000;Nonokawa et al, 2007).…”
Section: Kinetin and Potassium Nitrate Effects On Agronomic Characterunclassified
“…Management practices such as the application of Figaron may minimize the loss of soybean yield caused by water deficit. Cytokinins are reported to increase pod set in soybean Dyer et al, 1987;Kokubun and Honda, 2000). The combined effects of cytokinins and water deficit on pod retention and yield in soybean should be examined in future.…”
Section: Discussionmentioning
confidence: 99%